Mapping Problem-Based Learning Evolution in Economics Education: A Bibliometric Review - Channa Chamdiyah Atsaniyah; Riza Yonisa Kurniawan; Eka Indah Nurlaili (Research, Training and Philanthropy Institution Natural Aceh, 2026)
PBL is a relevant learning model to address the challenges of the 21st century. However, research on PBL mapping in the economic field has not been conducted. This research aims to fill this gap. The research data were obtained from the Scopus database and analyzed using Biblioshiny. The analysis includes annual publication trends, thematic mapping, country contributions, and keyword co-occurrence analysis. The results of the study show that publication trends have fluctuated, with a peak in 2020. The thematic mapping revealed that the research's core themes remain problem-solving, higher education, and teaching economics, with the emergence of new themes, namely technology integration, sustainability, machine learning, and effectiveness. Sierra J was recorded as the most prolific writer, while the highest publication contributions came from Indonesia, the United States, and Germany. The keywords that most often appear together include economics, human, and higher education. These findings show a shift in the research paradigm towards more context-based, digital, and sustainability-oriented economic learning and serve as the basis for future PBL research development.